Self-powered flexible sensors: from fundamental mechanisms toward diverse applications - Jingjing Chen; Jiangshan Zhang; Nuo Xu; Mengmeng Chen; Ju-Hyuck Lee; Yu Wang; Qijun Sun; Baolin Liu; Zhixian Gao (International Journal of Extreme Manufacturing)
Today, energy is essential for every aspect of human life, including clothing, food, housing and transportation. However, traditional energy resources are insufficient to meet our modern needs. Self-powered sensing devices emerge as promising alternatives, offering sustained operation without relying on external power sources. Leveraging advancements in materials and manufacturing research, these devices can autonomously harvest energy from various sources. In this review, we focus on the current landscape of self-powered wearable sensors, providing a concise overview of energy harvesting technologies, conversion mechanisms, structural or material innovations, and energy storage platforms. Then, we present experimental advances in different energy sources, showing their underlying mechanisms, and the potential for energy acquisition. Furthermore, we discuss the applications of self-powered flexible sensors in diverse fields such as medicine, sports, and food. Despite significant progress in this field, widespread commercialization will necessitate enhanced sensor detection abilities, improved design factors for adaptable devices, and a balance between sensitivity and standardization.